Indonesia Medical Council’s Secretariat: Performance Assessment of Non-Tax State Revenue Management - Sri Sundari; Fitria Ariyani (Jurnal Mantik, 2021)
The main purpose from this research is to assess the performance of the management of Non-Tax State Revenue (PNBP) at the Indonesian Medical Council's secretariat during 2017-2019 in order to amend the work unit so in the future the PNBP management will be even better. This research used descriptive qualitative method with respondents from the officials of Indonesian Medical Council. Those informant selection techniques used typical case sampling. This research model was applied to summative evaluation model then evaluated by before and after comparisons. The results from this research assessment are the PNBP management receipts have been performed accordingly to the applicable laws and regulations, but there are still leaking at the PNBP management and administration process. Several factors caused of declined in the performance such as the determination of the target indicator for the number of Registration Certificates (STR) which seems incompleted on time, the absence of reconciling data mechanism on PNBP and STR receipts that have been issued, and the absence of standard operational procedure (SOP) which valid relates to the mechanism for data reconciliation and PNBP accruals numbers and lastly is the necessity to increase the capacity of human resources who process the PNPB data.